2022
DOI: 10.3389/fpsyg.2022.1023366
|View full text |Cite
|
Sign up to set email alerts
|

Paranoid beliefs and conspiracy mentality are associated with different forms of mistrust: A three-nation study

Abstract: Paranoia and conspiracy are terms typically used interchangeably. However, although the underlying content of these types of beliefs might be similar (e.g., seeing others as powerful and threatening), recent research suggests that these constructs differ in important ways. One important feature shared by both constructs is excessive mistrust but this aspect might play different roles in each belief system. In this study we explored the strength of associations of different trust predictors (i.e., trust in inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…In the context of the COVID-19 pandemic, overarching epistemic mistrust also represents a key factor contributing to the increased prevalence of conspiracy beliefs (Magarini et al ., 2021 ). Specific examples of such associations include the correlation between conspiracy mentality and mistrust in scientific institutions and health organizations, resulting in reduced compliance with preventive guidelines (Plohl & Musil, 2021 ); mistrust in democratic political institutions and non-populist governments (Martinez et al ., 2022 ; Pickel et al ., 2022 ); and mistrust in conventional media platforms and news outlets, particularly when coupled with increased social media use (van der Linden et al ., 2020). These correlations between mistrust in various societal authorities responsible for information dissemination and conspiracy beliefs have been corroborated in multinational, representative samples (De Coninck et al ., 2021 ) and concerning both general and specific COVID-related CTs (Freeman et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of the COVID-19 pandemic, overarching epistemic mistrust also represents a key factor contributing to the increased prevalence of conspiracy beliefs (Magarini et al ., 2021 ). Specific examples of such associations include the correlation between conspiracy mentality and mistrust in scientific institutions and health organizations, resulting in reduced compliance with preventive guidelines (Plohl & Musil, 2021 ); mistrust in democratic political institutions and non-populist governments (Martinez et al ., 2022 ; Pickel et al ., 2022 ); and mistrust in conventional media platforms and news outlets, particularly when coupled with increased social media use (van der Linden et al ., 2020). These correlations between mistrust in various societal authorities responsible for information dissemination and conspiracy beliefs have been corroborated in multinational, representative samples (De Coninck et al ., 2021 ) and concerning both general and specific COVID-related CTs (Freeman et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are also more prone to perceive fake news headlines as accurate and to disseminate them on social media (Tanzer et al ., 2021 ). Cross-national large-scale studies have found a positive association between higher conspiracy mentality levels and a tendency to trust informal sources ( e.g ., internet websites and social media) for information about COVID- 19 (Martinez et al ., 2022 ; van Mulukom et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings align with previous research. For instance, Martinez et al (2022) demonstrated a relationship between suspiciousness, paranoia, and trust in informal sources of information, such as social media. When individuals disregard information from well-established institutions, conspiracy theorists seek alternative explanations for events (Pierre, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the pathological dimensions of personality, Martinez et al (2022) demonstrated that paranoia, rather than a conspiratorial mindset, was linked to trust in informal sources of information.…”
Section: Fake News and Personality Factorsmentioning
confidence: 99%
See 1 more Smart Citation